Isolation and characterization of Salmonella enterica associated with diarrhea in chickens and ducks in Hai Duong province - Quyen, Dong Van; Lanh, Pham Thi; Oanh, Nguyen Kim; Khang, Tran Nam (Vietnam Journal of Biotechnology, 2024)
Salmonella infections, or salmonellosis, represent a significant threat to poultry health and the global poultry industry, leading to considerable economic losses and serving as a major source of foodborne illnesses in humans and animals. Identifying the specific strains present in local poultry farms is crucial for implementing targeted interventions, including the development of effective biosecurity measures, vaccination strategies, and treatment protocols to mitigate outbreaks. This study focuses on isolating and characterizing Salmonella strains associated with diarrhea in chickens and ducks in Hai Duong province, Vietnam. The Salmonella strains were initially isolated using a culture-based method, followed by identification and characterization through Matrix-Assisted Laser Desorption Ionization/Time of Flight (MALDI-TOF), PCR amplification of the invA gene, and 16S rRNA gene sequencing. As a result, 18 Salmonella isolates were obtained, all of which contained the invA gene, indicating its potential significance in Salmonella pathogenesis. Analysis of the 16S rRNA gene sequences confirmed that all isolates belonged to the species Salmonella enterica, a well-known causative agent of intestinal diseases in humans and animals. Furthermore, phylogenetic analysis revealed that all 18 isolates grouped with Salmonella enterica subsp. enterica strains from China and Korea, suggesting a close relationship with strains circulating in the broader Southeast Asian region. This regional similarity may be attributed to the movement of poultry and poultry products, facilitating the cross-border spread of Salmonella. Our findings underscore the importance of implementing robust biosafety measures throughout the poultry production chain to control the spread of Salmonella, thereby enhancing both animal and food safety.